Staff's perception of Patients' affiliation and control in a Highly Secure Psychiatric Setting. (March 2019) - de Vries, Meike Godelieve; Brazil, Inti Angelo; Verkes, Robbert-Jan; Bulten, Berend Hendrik
Highlights: Patients' level of affiliation, as perceived by staff members, is positively associated with patients' age and negatively with recent problems with treatment response. Patients' level of control, as perceived by staff members, is positively associated with patients' engagement in disruptive behavior within the facility and negatively with symptoms of psychiatric illness. The level of patients' affiliation, as perceived by staff members, is positively associated with patients' reported satisfaction with daily staff. Abstract: Effective interactions between patients and staff have been associated with positive ward climate and therapeutic effects, but also pose a challenge in high secure forensic psychiatric settings. The goal of this study was to gain more insight into i) the characteristics that play a role in how staff members perceive the interpersonal style of patients, and ii) whether these perceptions are related to patients' evaluation of ward climate and satisfaction with daily staff. Staff members (n = 69), rated the interpersonal style of 102 male patients. Satisfaction with daily staff and ward climate were rated by 45 patients. Results show that patient characteristics (primary diagnosis, patient age, disruptive behavior, recent problems with symptoms of major mental disorder and recent problems with treatment or supervision response) were related to how staff perceived the interpersonal style (i.e., affiliation and control) of patients. Furthermore, the level of affiliation was positively related to patients' satisfaction with daily staff. Patients that were seen as more controlling by staff were less satisfied with the safety on their ward (as a factor of ward climate). The results indicate that perception of patients' interpersonal style entails patient related information and can be relevant for staff to use in their work.